YY1 and RTCB in mouse uterine decidualization and embryo implantation. Issue 6 (10th November 2021) - Li, Ran; Song*, Xiao-Tong; Guo, Si-Wei; Zhao, Na; He, Mei; He, Cheng-Qiang; Ding, Nai-Zheng
Abstract : As a multifunctional transcription factor, YY1 regulates the expression of many genes essential for early embryonic development. RTCB is an RNA ligase that plays a role in tRNA maturation and Xbp1 mRNA splicing. YY1 can bind in vitro to the response element in the proximal promoter of Rtcb and regulate Rtcb promoter activity. However, the in vivo regulation and whether these two genes are involved in the mother–fetal dialogue during early pregnancy remain unclear. In this study, we validated that YY1 bound in vivo to the proximal promoter of Rtcb in mouse uterus of early pregnancy. Moreover, via building a variety of animal models, our study suggested that both YY1 and RTCB might play a role in mouse uterus decidualization and embryo implantation during early pregnancy.